Language Variety Use in the Learning Process of Indonesian Language for Junior High School Students - Indah Afrianti; Nur Wahyuni; Arifin; Febi Latifa; Fadhillah; Ferdianto; Yerin Aulia; Nur Fania Alfisyah (Jurnal Pendidikan Indonesia, 2026)
This study is motivated by the suboptimal management of language variety use in Indonesian language instruction, which may affect communication effectiveness and students’ academic language mastery. Language variation naturally occurs in classroom interaction however, it is not always pedagogically managed to support instructional objectives. This study aims to analyze the use of language varieties in Indonesian language learning at the junior high school level using a mixed method approach. The quantitative approach was employed to identify the frequency and percentage of language variety use through structured observation and questionnaires, which were analyzed using descriptive statistics. Meanwhile, the qualitative approach was applied to describe the forms and contexts of language use through note taking techniques, participant observation, interviews, and documentation, which were analyzed using an interactive analysis model. The data were derived from teachers’ and students’ utterances during classroom instruction. The results reveal four types of language varieties, namely dialectal, formal, casual, and intimate varieties, with formal and casual varieties being dominant in classroom interaction. These findings indicate that learning takes place in a varied and contextual manner, influenced by instructional goals, communicative situations, and classroom interaction dynamics. The study implies the importance of proportional and context aware language management to support students’ communicative competence and academic language development.